The formal EU-US Meniscus Rehabilitation 2024 Consensus. An ESSKA-AOSSM-AASPT Initiative. Part I –Rehabilitation Management After Meniscus Surgery (Meniscectomy, Repair, Reconstruction) - Nicolas Pujol; Airelle O. Giordano; Stephanie E. Wong; Philippe Beaufils; Juan Carlos Monllau; Elanna K. Arhos; Roland Becker; Francesco Della Villa; J. Brett Goodloe; James J. Irrgang; Jitka Klugarova; Emma L. Klosterman; et al. (International Journal of Sports Physical Therapy)
# Purpose